Designing and Simulating Micro Fluxgate Sensor - MUHAMAD HILMI BIN SUFYAN, MUHAMAD HILMI (Universiti Teknologi Petronas, 2009)
The objective of this project is to design a micro fluxgate sensor using Coventorware software. This project is focusing on designing a fluxgate sensor in micro scale for sensing the magnetic field. Micro fluxgate sensor can be widely applied in the conventional and potential fields, for examples, scientific research, automation, process control of industry, mineral prospecting, medical appliance and satellite missions. The collection of technical details and data regarding the harmonics of magnetic field, micro fluxgate sensor and its conditioning circuit existing in the world is done. A 3D model of micro fluxgate sensor is designed using Coventorware software in its Architect and Designer applications. A simple analysis of micro fluxgate sensor is carried out to after designing the 3D model of micro fluxgate sensor.